La evaluación desde los practicantes del Programa de Educación Física, Recreación y Deportes de la Universidad de Caldas (2010)
ABSTRACT: Several authors have written about evaluation in Education, considering it is a complex, rigorous, thoughtful, dynamic, systematic and even ethical process, seeking knowledge acquisition, learning self-regulation, and the adoption of strategies, tools and decision making. This project explains description, interpretation and understanding of ideas and assessment practices by trainees from planning and staging on the courtyard. Work makes part of a qualitative approach, an emerging design supported on encoding to grasp ideas, and assessment practices applied by future physical educators. A ttriangulation process is performed to end with conclusions and suggestions emerging from the construction of meaning.